1996
DOI: 10.1021/bk-1996-0622.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Nanodispersed Metal Particles in Polymeric Matrices

Abstract: Three routes to the preparation of nanodispersed metal or metal oxides particles in polymer matrices have been studied. Thermal treatment in air of W-, Mo-and Cr-carbonyl complexes with polyacrylonitrile (PAN) results in the formation of nanometer-size metal oxide particles in a polycyclic polymer. Co-containing polymers were prepared by mixing Co 2 (CO) 8 with a PAN copolymer or an aromatic polyamide in dimethylformamide (DMF). Co 2 (CO) 8 interacts with DMF giving the complex [Co(DMF) 6 ] 2+ [Co(CO) 4 ] -2 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Recently, fabrication of inorganic nanoparticles in solid polymer matrixes has attracted more and more attention because the combination of inorganic nanoparticle and polymer provides a simple route to stable and processable materials integrating the promising properties of both components. However, these composites normally cannot be redissolved while preserving the colloidal state of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fabrication of inorganic nanoparticles in solid polymer matrixes has attracted more and more attention because the combination of inorganic nanoparticle and polymer provides a simple route to stable and processable materials integrating the promising properties of both components. However, these composites normally cannot be redissolved while preserving the colloidal state of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Such polymer-immobilized p-allylic complexes undergoing thermal decomposition can form nanoparticles in polymer [68], during which the thermolysis can be carried out even without a solvent (for example, by heating of the formed metallopolymer films using an infrared lamp). The nanoparticle sizes depend on many factors such as the characteristics of the used dispersant polymer, its molecular mass (the optimal value is M w ª 100,000), and the nature 5 Isotactic PP (melt) 5% Fe 63-65 Fe(CO) 5 Atactic PP (melt) 5-30% Fe 63-65 Fe(CO) 5 PE (melt) 1-29% Fe; 1.5-7 63-65 Cr(CO) 6 PTFE (fluoroplast-0.5-4% Cr; 1-5 63-65 40) (melt) of functional groups (L) and solvent.…”
Section: The Formation Of Metal Sols In Polymers By Thermal Decomposimentioning
confidence: 99%
“…Watkins and McCarthy 5 prepared nanocomposites of platinum and poly(4-methylpent-1-ene) I by exposing I to a solution of dimethyl(cyclooctadiene)platinum in supercritical fluid CO 2 for 4 h and subsequent reduction of platinum. Bronstein et al 6 reported a method for the preparation of polymer-cobalt nanocomposites by mixing Co 2 (CO) 8 with a polyacrylonitrile copolymer or an aromatic polyamide in dimethylformamide (dmf). Co 2 (CO) 8 interacts with dmf giving the complex [Co(dmf) 6 ] 2+ [Co(CO) 4 ] 2 2 , which is converted to nanodispersed Co particles by thermolysis.…”
mentioning
confidence: 99%